(untitled) (Applied Biological Research, 2019)
In this study, electrocardiographic assessment of turkey (Meleagris gallopavo) was undertaken and the reference values and configurations established using apparently healthy unanesthetized turkey. The waveforms of 12 healthy turkeys, presented to Avian, Exotic and Special Species Medicine, Unit of Veterinary College & Research Institute, Orathanadu (Tamilnadu), were analyzed in all the leads at 25 mm sec-1 or 50 mm sec-1 and 20 mm mV-1 or 10 mm mV-1. The heart rate ranged from 210-272 beats min-1 with mean value of 252.5 ± 16.73 min-1. PR interval was higher in females than in male turkeys. QT interval was found to be 0.146 ± 0.008 sec. The ECG values and patterns recorded in clinically healthy turkeys is expected to help in better understanding of ECG changes during diseases and shall serve as a comparison tool in clinical decision making.